Decoding key antecedents, moderators, and consequences of herd behaviour to predict consumers’ behaviour intentions: a systematic literature review - Zulfikar, Rizka; Hussein, Ananda Sabil; Suryadi, Nanang (Serbian Journal of Management, 2025)
This study conducted a systematic literature review to identify the antecedents, moderators, and consequences of herd Behaviour in marketing. The urgency of the research arose from the growing influence of social dynamics in digital consumer environments, where individuals increasingly relied on peer Behaviour and social proof to guide decisions. Drawing upon the TCCM (Theory, Context, Characteristics, and Methodology) and PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) frameworks, a total of 183 peer-reviewed articles published between 2000 and 2024 were analysed to ensure methodological rigour and thematic coherence. The review revealed that herd Behaviour in marketing is shaped by key antecedents such as homophily, trust, product uncertainty, and consumer interaction. These factors trigger herd tendencies and moderate their intensity across different contexts. In turn, herd Behaviour significantly influences consumer outcomes, including purchase intentions, impulse buying, and brand engagement. The study highlighted how marketers can strategically leverage herd mechanisms, such as user-generated content, influencer endorsements, and real-time social proof, to enhance consumer persuasion and brand loyalty. By synthesising fragmented insights across disciplines, this research offers a robust theoretical foundation for future investigations into socially influenced consumer Behaviour. It contributes to developing more adaptive marketing strategies in increasingly networked marketplaces